Evaluasi Biaya Penerapan Tanggung jawab sosial Dan Efisiensi Biaya Operasional Perusahaan Pada Pt Bukit Asam (Persero), Tbk - Fredericha Retno Dheta Tri Anggraeni (Master in Accounting Program, 2017)
Implementation of tanggung jawab sosial as well as environmental management activi-ties has become a thing that must be done by the company, demanding the company to spend more for the activities. This forces the company to perform efficiency in terms of management activities, as well as in terms of cost. When linked to tanggung jawab sosial and environmental management activities, the concept of efficiency can aim for the creation of more environmental-ly friendly goods and services, while reducing costs and improving environmental conditions. One of the efforts towards operational cost efficiency that can be done by the company is by syn-ergizing the business activities of tanggung jawab sosial partners with the company's operation-al activities.This research was conducted at PT Bukit Asam (Persero), Tbk Tanjung Enim, using de-scriptive study approach. The data collection was performed by means of observation, direct in-terview with related parties, and documentation. The results of this study indicate that the disbursement of funds for the tanggung jawab sosial each year in is accordance with the program contained stipulated in the ministerial regulations, including the imposition of funds for social responsibility activities that are charged as corporate expenses. Moreover, there are still tanggung jawab sosial activities that have not been effective, especially the tanggung jawab sosial activities in 4 villages, namely Kebur Village, Merapi Village, Telatang Village, and Muara Maung Village. The operational cost efficiency strategy implemented by PTBA is quite efficient, but there are still operational cost efficiency strategies that have not been effective, such as the cost efficiency strategies synergized with the Corporate social responsiblity partners. PT Bukit Asam (Persero) Tbk is expected to continue making improvement efforts in carrying out Corporate social responsibility activities as well as in implementing the company's operational cost efficiency strategies.